Medieval Sunni historians on Fatimid policy and non-Muslim influence. Issue 3 (27th May 2019) - Yarbrough, Luke
ABSTRACT: Modern historians routinely cast the Fatimid era in Egypt and Syria as a time when flourishing non-Muslim communities enjoyed an unusual degree of influence in the state. To complement the theme of this special issue – the real and perceived influence of minority out-groups in medieval societies – this essay examines representations of non-Muslim influence in the Fatimid period by post-Fatimid Sunni authors. Such representations do not reflect pervasive hostility among Sunni historians to Shiʿis or non-Muslims. Instead, they are quite diverse and not pervaded by sectarian antagonism. They are best understood within the contemporary 'social logic' of the works that contain them. At times their authors simply transmitted earlier sources intact; at others they had narrative goals that superseded their implicit views of either the Fatimids or their Jewish, Christian and Samaritan subjects.